2021
DOI: 10.1055/s-0040-1722323
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Meniscus Height and ACL Reconstruction Failure: A Nested Case–Control Study

Abstract: Previous work has shown that the morphology of the knee joint is associated with the risk of primary anterior cruciate ligament (ACL) injury. The objective of this study is to analyze the effect of the meniscal height, anteroposterior distance of the lateral tibial plateau, and other morphological features of the knee joint on risk of ACL reconstruction failure. A nested case–control study was conducted on patients who underwent an ACL reconstruction surgery during the period between 2008 and 2015. Cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 6 Failure to diagnose posterior lateral meniscus zip lesion or inadequate repair may lead to loss of concomitant ACL reconstruction. 7 Systemic arthroscopic exploration of the PL compartment is essential for identifying these hidden lesions. 8 Stable repair for this lesion is necessary to prevent further tear progression.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Failure to diagnose posterior lateral meniscus zip lesion or inadequate repair may lead to loss of concomitant ACL reconstruction. 7 Systemic arthroscopic exploration of the PL compartment is essential for identifying these hidden lesions. 8 Stable repair for this lesion is necessary to prevent further tear progression.…”
Section: Discussionmentioning
confidence: 99%
“…If the lateral meniscus is not repaired in time, the reconstructed ACL may remain unstable after surgery. 2 Recent studies have shown that small longitudinal tears of the lateral meniscus get worse over time regardless of the integrity of the ACL. 3 Therefore, lateral meniscus injuries should be recommended for careful surgical suturing if necessary.…”
Section: Introductionmentioning
confidence: 99%